The resource rent in Norwegian aquaculture 1984-2020: Calculations applying the National Accounts - Mads Greaker; Lars Lindholt (Statistics Norway, Research Department, 2021)
Extraordinarily high returns in a sector based on the extraction of a natural resource can be referred to as resource rents. This study uses the National Accounts and the definitions of the System of Environmental-Economic Accounting to calculate the resource rents in Norwegian aquaculture in the period 1984-2020. If we know the remuneration of all input factors such as capital, labour and technology except the remuneration of the aquacultural services, the resource rent will appear as the difference between the value of output and the remuneration of all other input factors. We argue that we are to a large extent able to separate other input factors from aquacultural services. We perform various sensitivity analysis as introducing higher rates of return, applying alternative wage costs and by treating the stock of fish as real capital. A robust conclusion is that there has been a significant resource rent in aquaculture since 2000 and that it has risen markedly since 2012. In the period 2016-2020 it has averaged 18-20 billion NOK.
Keywords: Q22; L11; E22; 330; Resource rent; aquaculture; National Accounts; System of Environmental-Economic Accounting